Brand Orientation as a Strategy That Influences the Adoption of Innovation in the Bottom of the Pyramid Market1. (20th May 2013) - Rahman, Mizan; Hasan, Md Rajibul; Floyd, David
Abstract If brand orientation is used as a strategy ensuring the "relative advantage" attribute of an innovation in the "bottom of the pyramid" market, it may influence the adoption of an innovation in the developing and emerging economies.